2021
DOI: 10.1155/2021/9026918
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of an Epithelial-Mesenchymal Transition-Based Signature in Gastric Cancer by Genomics and Prognosis Analysis

Abstract: Objective. Epithelial-mesenchymal transition (EMT) exerts a key function in cancer initiation and progression. Herein, we aimed to develop an EMT-based prognostic signature in gastric cancer. Methods. The gene expression profiles of gastric cancer were obtained from TCGA dataset as a training set and GSE66229 and GSE84437 datasets as validation sets. By LASSO regression and Cox regression analyses, key prognostic EMT-related genes were screened for developing a risk score (RS) model. Potential small molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Among them, PCOLCE2, ERP27, PSMD13, C14orf39, C16orf86, UGCG, and HPX were identified as prognostic factors for glioma for the first time. PCOLCE2 has been identified as a biomarker in multiple cancers, including colorectal and gastric cancers (L. Xu et al, 2021). ERP27 is highly expressed in colorectal cancers, and its expression is correlated with patient survival (Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, PCOLCE2, ERP27, PSMD13, C14orf39, C16orf86, UGCG, and HPX were identified as prognostic factors for glioma for the first time. PCOLCE2 has been identified as a biomarker in multiple cancers, including colorectal and gastric cancers (L. Xu et al, 2021). ERP27 is highly expressed in colorectal cancers, and its expression is correlated with patient survival (Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…SERPINE1 is a member of the validated five-member EMT- or plasticity-related prognostic gene set in gastric cancer and the six-gene signature that accurately predicts reduced overall survival in patients with HNSCC, where it partitions to the aggressive tumor signature subset, indicative of poor prognosis and higher risk score. SERPINE1 is generally classified as a hub or core gene in a wide spectrum of cancer types [ 50 , 118 , 141 , 146 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. For many of the poor outcome cancers, identification of SERPINE1 in the complement of hub or signature genes is a strong indicator of reduced patient survival [ 141 , 184 , 185 , 186 , 187 , 188 , 189 ].…”
Section: Caf-derived Pai-1 As a Poor Prognosis Biomarkermentioning
confidence: 99%
“…Functional analyses have revealed that most DEGs are predominantly involved in the ECM-receptor interaction pathway (20,21). Notably, Liu et al previously performed a graph-based clustering analysis and found that the ECMreceptor interaction pathway was correlated with the underlying molecular mechanisms of GC development (22).…”
Section: Discussionmentioning
confidence: 99%